A case of shoulder joint Streptobacillus moniliformis septic arthritis with severe subdeltoid bursitis. (July 2014) - Fansa, Ashraf Maher; Tanios, Mina; Ebraheim, Nabil
Abstract : Objective and importance: People in close contact with rodents, particularly those with rodents as pets, may become infected with the Streptobacillus moniliformis organism. Such patients may present with a triad of fever, rash, and arthritis. This medical condition is also known as rat-bite fever. It is imperative for the clinician to consider and recognize rat-bite fever in cases of septic arthritis in order to prevent delay in treatment. Severe involvement of the bursa requiring its excision during joint irrigation and debridement surgery has not been reported in the literature. Clinical presentation: We are reporting on a recent case of septic shoulder arthritis and severe subdeltoid bursitis due to rat-bite fever in a 19-year-old female. Pre-operative magnetic resonance imaging scans demonstrated severe bursal involvement. Intervention: In addition to antibiotics, excision of the bursa was necessary in this case in combination with irrigation and debridement of the joint. Conclusion: The bursa adjacent to the involved joints in cases of rat-bite fever should be thoroughly investigated. Their severe involvement may necessitate their excision during the initial irrigation and debridement procedure.